``On the basis of information supplied by the Soviet friends...'' The Slavist Dean S. Worth and operation ``Dean'' of the Czechoslovak State Security - Dittmann, Robert (Bohemica Olomucensia, 2019)
The contribution describes in detail the operation Dean, carried out by the Czechoslovak Communist State Security in the early 1970s, following incentives submitted by the KGB and focusing on the Slavist Dean Stoddard Worth (1927-2016). The KGB was tracking Worth since his early visits in the post-Stalin Soviet Union in 1957 and managed to copy addresses of Czechoslovak citizens from his notebook which the Soviets sent to the Czechoslovak authorities. Worth visited Czechoslovakia several times and during his 1972 visit, he was closely followed by the Czechoslovak Communist State Security. Even though the counter-intelligence agents even entered Worth's room, no subversive and espionage activities were proven. The operation is documented by materials stored in the Archives of Security Services in Prague, Czech Republic, and its analysis contributes to the ``hidden history'' of linguistics during the Czechoslovak Communist regime.
Keywords: Dean Stoddard Worth; KGB; Czechoslovak State Security